The riboflavin-photosensitized degradation of the uv-absorbing azo dye-metabolites Benzidine and o-Tolidine. Kinetic and mechanistic aspects - Morales, María Gisela (2017)
The visible-light-promoted photodegradation of two carcinogenic primary azo-dye metabolites (BZ-C), represented by the colourless water-contaminants Benzidine (BZ) and o-Tolidine (OT), was studied in water-methanol solution. It was done in the presence of air and the natural pigment riboflavin (Rf) as a photosensitizer. These conditions reasonably mimic a natural environment scenery. Both BZ-C interact with the reactive oxygen species (ROS) singlet molecular oxygen (O2(1Δg)), superoxide radical anion (O2[rad]–), hydrogen peroxide (H2O2) and hydroxyl radical (OH[rad]), all photogenerated in situ through energy-transfer and electron-transfer processes. The interaction of BZ-C with O2(1Δg) is essentially physical in nature and occurs with a relatively high rate constant value. The effective BZ-C degradation is mainly driven by the remaining photogenerated ROS. A comparison of the BZ and OT photooxidative-rate with those of the archetypal surface-water-contaminants aniline and phenol indicates that BZ-C degradation occurs in a moderately slower fashion than the reference contaminants, within a common overall time-scale. The primary photoprocesses initiating the Rf-sensitized degradation seems to be quite similar for the four compounds, with the simultaneous operation of Type I and Type II photoprocesses. In conclusion: the natural Rf- photosensitized degradation of BZ-C appears as a plausible process, as evaluated under simulated environmental conditions.